Where's the Remote? Failure to Report Clinical Workflows in Heart Failure Remote Monitoring Studies - SHALOWITZ, ELISE L.; JHUND, PARDEEP S.; PSOTKA, MITCHELL A.; SHARMA, ABHINAV; DIMOND, MATTHEW G.; MARTYN, TREJEEVE; NKULIKIYINKA, RICHARD; FIUZAT, MONA; KAO, DAVID P. (Journal of cardiac failure, 2025)
•Device characteristics are well described in heart failure remote patient monitoring (RPM) studies.•Clinical workflows in response to RPM data are reported incompletely, if at all.•A standardized approach to reporting workflows in RPM trials is urgently needed. Remote patient monitoring (RPM) clinical trials have reported mixed results in improving outcomes for patients with chronic heart failure (HF). The impact of clinical workflows that could impact RPM effectiveness is often overlooked. We sought to characterize workflows and response protocols that could impact outcomes in studies of noninvasive RPM in HF. We reviewed studies (1999–2024) assessing noninvasive RPM interventions for adults with HF. We collected 24 aspects of workflows describing education, physiologic and symptomatic data collection, transmission and review, clinical escalation protocols, and response time. We attempted to perform a meta-analysis to identify associations between workflow components and outcomes of death and hospitalization. We identified 63 studies (57.1% randomized controlled, 23.8% pilot/feasibility, 19.1% other) comprising 16,699 subjects. Despite a large number of studies and subjects, workflow reporting was insufficient to perform our intended meta-analysis regarding key workflow components. RPM clinical workflows were diverse in configuration, with high variability in component description ranging from always reported to never reported. Specifics of monitoring devices and related training were well reported as expected based on most trial hypotheses. However, elements of clinical data response such as frequency of data review, clinical escalation criteria, and provider response time were often underreported or not reported at all (48%, 24%, and 97%, respectively), hindering study replication and evidence-based implementation. Clinical workflows are poorly described in noninvasive RPM studies, preventing systematic assessment, device comparison, and replication. A standardized approach to reporting HF RPM workflows is vital to evaluate effectiveness and guide evidence-based clinical implementation. [Display omitted] Visual Take Home Graphic: RPM programs are highly complex and require multifaceted clinical workflows. However, key aspects are often poorly reported or not reported at all.